Holocene succession patterns of land snails across temperate Europe: East to west variation related to glacial refugia, climate and human impact - Horsák, Michal; Limondin-Lozouet, Nicole; Juřičková, Lucie; Granai, Salomé; Horáčková, Jitka; Legentil, Claude; Ložek, Vojen (Palaeogeography, palaeoclimatology, palaeoecology, 2019)
Although Holocene mollusc succession has been described from many temperate European sites, no attempt to analyse diversity patterns across the continent from east to west has yet been done. Here, we assembled and quantitatively analysed 54 most representative Holocene successions categorized into five climatic and geomorphological regions. These were defined along a longitudinal transect across temperate Europe, i.e. West Carpathians, Bohemian Massif, West Continental, Atlantic France, and Atlantic England. We found a clear east-west gradient in the Holocene dynamic of land snail assemblages, correlating mainly with the changes in strictly forest species richness. Representation of these species increased towards the east in accordance with known position of glacial refugia in the Carpathian Mountains. The West Carpathians acted as a unique refugium, expressing the highest temporal stability of Holocene snail assemblages, with a sharp increase in strictly forest species richness already in the Early Holocene. In contrast, Atlantic regions, characterized by low elevation and low topographical heterogeneity, were always poor in number of strictly forest species with no or only shallow increase of their richness in the Holocene climatic optimum. Further reduction in the second half of the Holocene, along with the increase of strictly open-country species richness correlates with higher human impact on mollusc faunas in lowland and flat regions. These factors can explain the previously reported impoverishment of modern western European forest fauna and have apparently also contributed to regional diversity patterns throughout the Holocene. Among the regions, we found three types of successional trajectories in the composition changes of Holocene molluscs, mirroring the above mentioned east-west gradient, with the West Carpathians having the most distinctive fauna. Our results show that distance from glacial refugia, landscape topography, and also human impact importantly shaped the species richness dynamic and successional pathways of Holocene land-snail fauna across temperate Europe. •Holocene mollusc succession was quantitatively analysed across temperate Europe.•Changes of forest species richness mirror distance from glacial refugia.•Mollusc fauna of lowland and flat regions was more affected by humans.•West Carpathian fauna was the most distinctive within temperate Europe.•Pathways of Holocene compositional changes in Europe differ from east to west.